Analisis Pengetahuan Cedera Dalam Pembelajaran PJOK Pada Siswa Kelas V SD Negeri Gembong 5 - Tito Pangesti Adji; Naela Khusna Faela Shufa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research uses a quantitative descriptive research design. The aim of this study was to assess the level of knowledge of Class V students at SDN Gembong 5 regarding injuries experienced while carrying out physical activities. This research will be carried out at SDN Gembong 5 which is located in Pati Regency, Central Java, in Gembong Village, Gembong District. The date of this research is May 16 2024. The research population is 48 class V students at SDN Gembong 5. In this research, total sampling was used for sampling. The level of knowledge of fifth grade students at SDN Gembong 5 regarding injuries experienced while carrying out physical activities is the dependent variable for the research. The multiple choice written test is the research instrument used in this research. Based on the results of this research, it can be concluded that the knowledge of Class V students at SDN Gembong 5 regarding injuries experienced when carrying out physical activities which are divided into three categories, namely sports injuries, injury prevention and injury treatment, have very high knowledge of the three categories tested.